Angiographic Severity of Coronary Artery Disease among Patients with Non-ST Elevated Acute Coronary Syndrome having Fragmented-QRS in ECG - Ferdous, Md Abu Raihan; Mandal, Mrm; Kabir, Faisal Ibn; Amin, Md Rasul; Ahsan, Syed Ali; Mahbub, Sm Ear E; Bhuiyan, Akm Mohiuddin; Rahman, Md Mukhlesur (University Heart Journal, 2020)
Fragmented QRS (f-QRS) complex in 12 lead ECG may develop in the background of acute coronary syndrome (ACS). This study was aimed to evaluate the angiographic severity of CAD among non-ST ACS patients having f-QRS in the ECG.This cross-sectional observational study was conducted in Cardiology department of BSMMU. Total 52 non-ST ACS patients who underwent invasive coronary angiography (CAG) were included in two groups according to presence or absence of f-QRS complex. 25 patients were included in f-QRS group and 27 in non-f-QRS group. After CAG, severity of CAD was assessed and compared by number of vessel involvement and degree of vessel stenosis. Patients’ demographic parameters were same in both groups. Depending on the number of vessel involvement, it was found that among f-QRS patient group, highest percentage had triple vessel (32%) followed by double vessel (28%) and single vessel (24%) disease and 16% patient had normal or non-critical epicardial coronary arteries. Among non-f QRS group, highest percentage had normal or non-critical lesions (40.7%) followed by double vessel (25.9%), single vessel (22.2%) and triple vessel disease (7.4%). In conclusion, this study revealed that presence of f-QRS in ECG is associated with more severe form of CAD and once the finding is observed, the particular patient should be targeted for aggressive management. University Heart Journal Vol. 16, No. 1, Jan 2020; 28-32